Storytelling to Support Agricultural-Based Tourism Villages - Aristiono Nugroho (Sahabat Publikasi, 2026)
Storytelling is a strategic instrument in supporting tourism villages based on agrarian resources, as happened in Pucung Village, Girisubo District, Gunungkidul Regency. The village faces challenges in promoting physical assets, such as karst landscapes and historical sites, into tourism products that have high economic value and educational meaning. Therefore, on November 25, 2025, in Pucung Village, an Agrarian Resource-Based Storytelling Making Training activity has been held. The research method used is a qualitative approach with data collection techniques through in-depth interviews with key informants, namely local narrators, tourism village managers, and the Pucung Village community. Secondary data was also obtained from documentation and reports related to storytelling training that had been carried out in the village. The data analysis technique used is thematic analysis, where data is categorized and linked to produce findings that are relevant to the research objectives. The results of the study show that: First, storytelling has a unique mechanism. Second, storytelling is intended to empower local narrators. Third, storytelling can reveal the soul of the people of Pudung Village. Fourth, storytelling is done by adhering to Truth Based Storytelling Principles. Fifth, storytelling can have a psychological and social impact. Sixth, storytelling can have an economic multiplier effect. Seventh, storytelling takes into account managerial strategy and sustainability.